Identifikasi Bakteri Salmonella sp. Pada Telur yang dijual di Pasar Kota Kendari Provinsi Sulawesi Tenggara - Satya Darmayani; Anita Rosanty; Vina Vanduwinata (Biogenesis: Jurnal Ilmiah Biologi, 2017)
This study aimed to identify the presence of Salmonella sp. in eggs sold in the market of Kendari. The World Health Organization (WHO) declared Salmonella sp. is a genus of bacteria that is a major cause of food borne illness in the entire world. Two factors that cause Salmonella sp. contained in eggs are internal and external factors that cause diarrhea or gastroenteritis. The sampling technique was done by purposive sampling, the population is the seller of eggs located in the market of Kendari city that is as much as 172 egg sellers with the sample size are 34 egg samples of chicken. In the process of planting samples on Brain Heart Infusion Broth (BHIB) media, all positive samples were cloudy, indicating bacterial growth in the sample. Furthermore, bacteria were inoculated in Salmonella Shigella Agar (SSA) medium which obtained negative results from 34 samples, no Salmonella sp. colony growth on SSA medium. So it can be concluded, the sample of chicken eggs in this study declared not contaminated by Salmonella sp.